A hero's guide to deadly dragons - Cowell, Cressida (London : Hodder Children's, 2010)
Hiccup is lost in the library labyrinth and the Driller-Dragons and Madguts the Murderous are on the prowl. This story also contains a Dragonese dictionary and dragon profile.
Originally published: 2007.
Keywords: Dragons -- Juvenile fiction; Haddock, Hiccup Horrendous, III (Fictitious character) -- Juvenile fiction; Vikings -- Juvenile fiction; Fantastic fiction; Children's stories